BELIZE AND THE RBGE: REFLECTING ON 16 YEARS OF COLLABORATIVE TRAINING. (18th July 2020) - Goodwin, Z. A.; Stott, G. L.; Ronse De Craene, L. P.; Kay, E.; Lopez, G. N.; Haston, E.; Harris, D. J.
Abstract : Between 2001 and 2017, the Royal Botanic Garden Edinburgh conducted training and research in Belize built around an annual two-week field course, part of the Edinburgh M.Sc. programme in Biodiversity and Taxonomy of Plants, focused on tropical plant identification, botanical-collecting and tropical fieldwork skills. This long-term collaboration in one country has led to additional benefits, most notably capacity building, acquisition of new country records, completion of M.Sc. thesis projects and publication of the findings in journal articles, and continued cooperation. Detailed summaries are provided for the specimens collected by students during the field course or return visits to Belize for M.Sc. thesis projects. Additionally, 15 species not recorded in the national checklist for Belize are reported. The information in this paper highlights the benefits of collaborations between institutions and countries for periods greater than the typical funding cycles of three to five years.